2012
DOI: 10.1111/j.1365-2125.2012.04296.x
|View full text |Cite
|
Sign up to set email alerts
|

Human microdose evaluation of the novel EP1 receptor antagonist GSK269984A

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The microdose administration of novel drug candidates to humans in early development is currently undergoing evaluation as a cost‐efficient approach to the early assessment of pharmacokinetics (PK) before the commitment of resources required to support formal phase 1 studies.• The microdose approach assumes that PK can be extrapolated linearly over the full range of exposures achieved with sub‐pharmacological doses up to the therapeutic dose range.• Few microdose studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The low doses administered obviously demand the use of highly sensitive analytical techniques in order to measure the plasma drug concentrations over sufficient time. The majority of human microdose studies reported in the literature have been conducted using 14 C-labelled drug and analysis conducted using the ultrasensitive isotope-ratio technique of AMS although studies have also been performed using non-labelled drug and sensitive LC-MS [35,36] and the relative merits of both techniques have been previously discussed [16]. The choice of analytical technique is largely driven by the expected plasma-drug concentrations and the limit of quantification of the analytical method.…”
Section: Analytical Methods Associated With Microdosingmentioning
confidence: 99%
See 1 more Smart Citation
“…The low doses administered obviously demand the use of highly sensitive analytical techniques in order to measure the plasma drug concentrations over sufficient time. The majority of human microdose studies reported in the literature have been conducted using 14 C-labelled drug and analysis conducted using the ultrasensitive isotope-ratio technique of AMS although studies have also been performed using non-labelled drug and sensitive LC-MS [35,36] and the relative merits of both techniques have been previously discussed [16]. The choice of analytical technique is largely driven by the expected plasma-drug concentrations and the limit of quantification of the analytical method.…”
Section: Analytical Methods Associated With Microdosingmentioning
confidence: 99%
“…In addition, for drugs in development, microdose studies can be performed before the drug might be administered at therapeutic doses and so it can be some time before the therapeutic data are published. There are therefore a number of accounts of microdosing in the literature where a therapeutic dose of drug has not yet been given [35,44,45]. A comprehensive summary of the peer-reviewed literature comparing human microdose with therapeutic dose pharmacokinetics is shown in Table 1 .…”
Section: The Utility Of Microdosingmentioning
confidence: 99%
“…Conflicting data from in vivo and/or in vitro experiments and inability to validate extrapolation methods Modelling and simulation produce results inconsistent with in vivo and/or in vitro data or with existing human data from related compounds given in therapeutic doses Inconsistent pharmacokinetic profiles 13,35,101,102,[104][105][106][107][108]119 Challenging allometric scaling due to high plasma protein binding 102 Demonstrated tumour penetration in contrast to preclinical data 109 Poor animal models of Alzheimer disease 9,10,100,117,126 Assessment of linearity across the microdose to therapeutic dose range in animals to enhance the validity of extrapolation 37,38 Toxicity/safety concerns Preclinical data suggest high toxicity potential (for example, binding to non-therapeutic targets)…”
Section: Candidate Selectionmentioning
confidence: 99%
“…5 shows how PGE2 induces intracellular signaling of EP1. Studies have reported EP1 agonists, such as ONO-8103, ONO-8359, GSK269984A, and GSK345931A, as EP1 inhibitors [35][36][37][38]. Each inhibitor alleviates bladder pain [35] or suppresses acid-derived heartburn symptoms [36] and inflammatory pain [38].…”
Section: Pge2-mediated Intracellular Signaling Of Ep1mentioning
confidence: 99%